"I speak english, but I am still me": the roles of the English language in Alter do Chão, Brazil - Souza, Silvia Cristina Barros de (2016)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão, Programa de Pós-Graduação em Inglês: Estudos Linguísticos e Literários, Florianópolis, 2016.